Inhibition behaviours of some phenolic acids on rat kidney aldose reductase enzyme: an in vitro study - Zuhal Alim; Namik Kilinç; Bülent Şengül; Şükrü Beydemir (Taylor & Francis Group, 2017)
Aldose reductase (AR) inhibitors have vital importance in the treatment and prevention of diabetic complications. In this study, rat kidney AR was purified 19.34-fold with a yield of 3.49% and a specific activity of 0.88 U/mg using DE-52 Cellulose anion exchange chromatography, gel filtration chromatography and 2'5' ADP Sepharose-4B affinity chromatography, respectively. After purification, the in vitro inhibition effects of some phenolic acids (tannic acid, chlorogenic acid, sinapic acid, protocatechuic acid, 4-hydroxybenzoic acid, p-coumaric acid, ferulic acid, vanillic acid, syringic acid, α-resorcylic acid, 3-hydroxybenzoic acid and gallic acid) were investigated on purified enzyme. We determined IC50, Ki values and inhibition types of these phenolic acids. As a result, tannic and chlorogenic acid had a strong inhibition effect. On the other hand, gallic acid had a weak inhibition effect. In this study, all phenolic acids except for chlorogenic acid and p-coumaric acid showed non-competitive inhibition effects on rat kidney AR.